P27 Patients with advanced COPD have unmet care and support needs across clinical settings: how can we identify needs to enable patient-centred care?. (12th November 2015) - Farquhar, MC; Gardener, AC; Moore, C; Holt Butcher, H; Ewing, G; White, P; Booth, S; Howson, S; Mahadeva, R
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is progressive, with high symptom- and carer-burden, accounting for one death every 20 min in England and Wales. Patient-centred care takes into account patient needs and preferences. Research on care and support needs in advanced COPD, and ways to identify them in clinical practice, is limited. Methods: We conducted mixed-method interviews with a population-based cohort of 235 well-characterised patients with advanced COPD (meeting 2/6 clinician-defined criteria) and their carers (n = 115 family and friends who support them), and qualitative interviews with purposively sampled key clinicians (n = 45; primary and secondary care). Quantitative data include validated patient measures of function, need and service use analysed using descriptive statistics. Purposively sampled multiple-perspective qualitative data on needs and experiences of care analysed using a framework approach. Results: Patients' mean age was 71.6 years (SD 10.3), 61% were male and 30% lived alone. Their mean MMRC dyspnoea scale was 3.68 (SD 1.04) and mean CAT score 23.4 (SD 7.5). Mean HADS anxiety and depression scores were higher than population norms: anxiety 7.31 (SD = 4.69); depression 6.72 (SD = 3.53). Patients identified symptoms they had not reported to clinicians; just over a fifth with self-identified anxiety/depression had not reported these. Patients had unmet needs for support with practical tasks, personal care, psychological support and information; their ability to spontaneously articulate needs was limited and we found little evidence of holistic needs assessment by clinicians. 20% could not identify a clinician who supported them. Service contacts were mainly in primary care and descriptions of service contacts (primary/secondary) could be characterised as predominantly reactive: the "care" element of contacts was invisible to some. Feelings and worries were rarely discussed. Service contacts appeared driven by organisational and medical agendas rather than patient-centred. Conclusions: Service contacts in advanced COPD are predominantly reactive and brief, with limited evidence of proactive engagement with patients and carers. Shifting the focus beyond organisational and medical agendas to a more patient-centred approach requires the proactive identification of patient need, prompted by clinicians. This could be facilitated by a brief structured holistic tool, grounded in patient data, for use across clinical settings.